Study of Lowest Odd Parity Configurations in Ge-I Like Ions (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Fine structure energy levels, transition probabilities and oscillator strength for terms belonging to the ground configuration, \(\rm 4s^{2}4p^{2}\) and the first exited odd parity configurations \(\rm 4s4p^{3}\), \(\rm 4s^24p5s\) and \(\rm 4s^{2}4p4d\) of Ge-I like ions have been calculated using Hartree-Fock method with relativistic correction incorporating large number of interacting configurations \(\rm[4s^{2}4p(4f+5p+5g), 4s4p^{2}(4d+5s), 4p^{3}(4d+5s)]\). Experimentally reported levels have been compared with theoretical results establishing energy parameters in the first eleven members of the sequence (Ge I-Mo XI). The configuration \(\rm 4s^{2}4p4d\) in Rb VI, Sr VII, and \(\rm 4s4p^3\) except \(\rm 4s4p^{3}\) \(\rm^{5}S_2\) level in Ge-I, are not observed yet. A systematic study of Slater parameters in the isoelectronic sequence enabled us to make precise predictions of the missing energy levels belonging to these configurations.
Keywords: Energy levels; Oscillation strength; ab initio calculations; Isoelectronic sequence; Transition probabilities